PENGARUH ARUS KAS OPERASI DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
This study aims to examine the effect of operating cash flow and accounting profit on stock returns on manufacturing companies listed on the Indonesia Stock Exchange. The data used in this study were 36 secondary data using a purposive sampling method. The method used to analyze between the independent variable and the dependent variable is the method of multiple linear regression and the classical assumption test. The results of the research partially operating cash flow have a significant effect on stock returns on Manufacturing Companies listed on the Indonesia Stock Exchange in the 2016-2018 period and accounting profit variable has a significant effect on stock returns on Manufacturing Companies listed on the Indonesia Stock Exchange in the 2016-2018 period. Simultaneously shows that operating cash flow and accounting profit have a significant effect on stock returns on Manufacturing Companies listed on the Indonesia Stock Exchange for the period of 2016-2018.